Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1002/jlb.61.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated U937 cells transfected with chemoattractant receptors: a model system to investigate chemotactic mechanisms and receptor structure/function relationships

Abstract: Abstract:Transfection of either the C5a receptor or the formylpeptide receptor into undifferentiated U937

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 32 publications
1
70
0
Order By: Relevance
“…All three mutants demonstrated binding of the fluorescent ligand N-formyl-Nle-Leu-Phe-Nle-Tyr-Lys-fluorescein at levels comparable to those of the wild-type receptor. Expression of the wild-type FPR in U937 cells has previously been shown to yield binding affinities for [ 3 H]fMLF similar to those of the FPR from dibutyryl cAMP-differentiated U937 cells and neutrophils (17). Detailed ligand binding studies performed here using [ 3 H]fMLF demonstrated that the mutant forms of the FPR exhibited both high and low affinity binding sites similar to those of the wild-type FPR (Table I).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…All three mutants demonstrated binding of the fluorescent ligand N-formyl-Nle-Leu-Phe-Nle-Tyr-Lys-fluorescein at levels comparable to those of the wild-type receptor. Expression of the wild-type FPR in U937 cells has previously been shown to yield binding affinities for [ 3 H]fMLF similar to those of the FPR from dibutyryl cAMP-differentiated U937 cells and neutrophils (17). Detailed ligand binding studies performed here using [ 3 H]fMLF demonstrated that the mutant forms of the FPR exhibited both high and low affinity binding sites similar to those of the wild-type FPR (Table I).…”
Section: Resultsmentioning
confidence: 58%
“…To investigate the mechanisms of cellular desensitization in response to fMLF, mutant forms of the FPR were generated lacking some or all of the potential phosphorylation sites contained within the carboxyl terminus and expressed in human myeloid U937 cells (17). The results presented here demonstrate that phosphorylation at multiple sites within the carboxyl terminus of the FPR is a necessary step in the desensitization of the receptor and that without it cells remain completely responsive to subsequent challenges with ligand.…”
mentioning
confidence: 91%
“…To investigate the potential interaction between the FPR and arrestins, we utilized a model promonocytic cell line, U937, stably transfected with the wild type FPR (23). Analysis of whole cell lysates by Western blot revealed that this cell line predominantly expresses arrestin-2 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were grown in RPMI 1640 (Invitrogen) supplemented with 10% heat-inactivated fetal bovine serum, 100 units/ml penicillin, 100 g/ml streptomycin, 10 mM HEPES, pH 7.4, 100 g/ml ciprofloxacin, 2 mM L-glutamine, at 37°C in a humidified atmosphere of 5% CO 2 and 95% air. Site-directed mutants of formyl peptide receptor in the human monoblastoid line U937 constitutively expressing human VLA-4 integrin were prepared as described (19). High expressors were selected using the MoFlo Flow Cytometer (Cytomation, Inc., Fort Collins, CO).…”
Section: Materials-thementioning
confidence: 99%